Impact of English Language on Academic Performance of Learners in Selected Primary Schools in Southern Division Kabale Municipality Kabale District. - Kyarimpa, Jackline (Kabale University, 2024)
This study sought to assess the impact of English language on academic performance of learners in selected primary schools in southern division Kabale municipality Kabale district. The study established the to find out the impact of English language on academic performance of learners in Southern Division Kabale Municipality Kabale District, to determine teachers' preparedness in their use of English language in teaching other subjects and to find out effects of English language enhancement on academic performance among primary schools. The study employed a cross¬sectional survey research design. The study sample included 20 teachers and 35 pupi Is drawn from 5 primary schools selected from Southern Division. Data collection was done using a questionnaire with both closed ended and open-ended questions. The collected data was analyzed in form of descriptive statistics and findings were presented in tables. The researcher therefore concluded that teacher's accent and pronunciation of certain words has led confusion and misinterpretation of questions thus poor performance. Employment of non-qualified staff can also end up causing poor. Learners' performance was also affected by failure to complete the syllabus, inadequate infrastructure such as libraries and computer laboratories as well as poor time management in addition to lows supervision. In order to improve pupils' performances, all stakeholders, that is the Ministry of education, the study recommends that supervisors which include District Education Officer, Uganda National Examinations Board, head teachers, teachers, learners and parents should be involved and work hand in hand and this will improve pupil' academic performance.